2022
DOI: 10.3389/fonc.2022.942064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic reprogramming and drug resistance in breast cancer

Abstract: Breast cancer is the leading cause of cancer death in women. At present, chemotherapy is the main method to treat breast cancer in addition to surgery and radiotherapy, but the process of chemotherapy is often accompanied by the development of drug resistance, which leads to a reduction in drug efficacy. Furthermore, mounting evidence indicates that drug resistance is caused by dysregulated cellular metabolism, and metabolic reprogramming, including enhanced glucose metabolism, fatty acid synthesis and glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 232 publications
0
1
0
Order By: Relevance
“…Through the phosphorylation of serine 19 by AMP kinase (AMPK) and inhibition of PDH kinase 4 (PDK 4), which inactivates PDH, E2 increases PDH activity. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Through the phosphorylation of serine 19 by AMP kinase (AMPK) and inhibition of PDH kinase 4 (PDK 4), which inactivates PDH, E2 increases PDH activity. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Different degrees of amino acid reprogramming were demonstrated in different types of BC. Specifically, the HER2 + subtype is one of the most glutamine metabolism-dependent subtypes, and the elevated levels of glutamine transporter protein (SLC1A5) and GLS transcripts in HER2 + breast cancers increased their dependence on glutamine metabolism, thus identifying new therapeutic targets for HER2 + breast cancers ( Lv et al, 2022 ). In addition, the overexpression of GLS in TNBC, which is highly resistant to Glutamine catabolism-targeted therapy was sensitive, with specific metabolic levels expressed as a low glutamine/glutamate ratio ( Wang et al, 2020 ).…”
Section: Targeting Amino Acid Metabolismmentioning
confidence: 99%
“…Several studies have demonstrated that metabolic reprogramming is a prominent feature in therapy resistance and aggressiveness in breast cancer cells. The metabolic milieu that characterizes T2D and often obesity provides a favorable microenvironment to support breast cancer growth, including sustained hyperglycemia and dyslipidemia ( 121 , 122 ).…”
Section: Metabolic Reprogramming In Aggressive Breast Cancer Cellsmentioning
confidence: 99%